Magmatic Response to Subduction Initiation, Part II: Boninites and Related Rocks of the Izu‐Bonin Arc From IODP Expedition 352 - John W. Shervais; Mark K. Reagan; Marguerite Godard; Julie Prytulak; Jeffrey G. Ryan; Julian A. Pearce; Renat R. Almeev; Hongyan Li; Emily Haugen; Timothy Chapman; Walter Kurz; Wendy R. Nelson; et al. (Geochemistry, Geophysics, Geosystems, 2021)
Abstract International Ocean Discovery Program Expedition 352 to the Izu‐Bonin forearc cored over 800 m of basement comprising boninite and boninite‐series lavas. This is the most extensive, well‐constrained suite of boninite series lavas ever obtained from in situ oceanic crust. The boninites are characterized as high‐silica boninite (HSB), low‐silica boninite (LSB), or basaltic boninite based on their SiO2‐MgO‐TiO2 relations. The principal fractionation products of all three series are high‐Mg andesites (HMA). Lavas recovered >250 meters below seafloor (mbsf) erupted at a forearc spreading axis and are dominated by LSB and HMA. Lavas recovered from <250 mbsf erupted off‐axis and are dominated by HSB. The axial and off‐axis lavas are characterized by distinct chemostratigraphic trends in their major, trace, and isotopic compositions. The off‐axis lavas are chemically similar to boninite from the type locality at Chichijima, with concave‐upward rare earth elements patterns. In contrast, the more abundant axial lavas have distinctly light rare earth element‐depleted patterns and represent a new, previously unsampled precursor to the Chichijima‐type boninite lavas. Petrogenetic modeling suggests that the axial lavas formed by fluxing of refractory mantle (likely the residue from forearc basalt extraction), with amphibolite‐facies melt derived from subducting altered oceanic crust. The upper, off‐axis lavas require an additional component of sediment‐derived melt in addition. Both models are consistent with previously published isotopic data.